Workforce environment and audit fees: International evidence. Issue 1 (April 2020) - Sun, Xuan Sean; Habib, Ahsan; Bhuiyan, Md. Borhan Uddin
Abstract: Using a dataset from 30 countries over the period from 2002 to 2017, we examine the effects of auditing clients' workforce environment on audit fees as well as the role that national labor market flexibility plays in this relationship. We find evidence that audit fees are significantly lower for firms with a good workforce environment, suggesting that auditors perceive such clients as less risky; as a result, auditors expend less effort and/or charge a lower risk premium. Furthermore, we find this effect to be stronger for firms in countries with a more flexible labor market. Our mediation test results indicate that the relationship between the audit client workforce environment and audit fees is mediated by media coverage of workforce controversies. Our study contributes to the international audit fee literature by identifying employee welfare as a distinct audit pricing factor, above and beyond the effects of overall corporate social responsibility practices.